2000
DOI: 10.1507/endocrj.47.77
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Correlation between Urine Nitric Oxide Metabolites and Insulin Resistance in Patients with Type 2 Diabetes Mellitus.

Abstract: Abstract.We studied the possible relationship between nitric oxide (NO) production and insulin resistance in patients with type 2 diabetes mellitus. Urine NO metabolites (NOx) were measured as an index for NO production by HPLC combined with a Cd column, Griess reaction and a spectrophotometer in 403 healthy control subjects and 102 hospitalized patients with type 2 diabetes. Glucose infusion rate (GIR) was measured as a reverse index for insulin resistance by euglycemic glucose clamp study using an artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…There is increasing evidence that NO synthesis and the vasodilating properties of insulin are impaired in insulin resistant states, such as Type II diabetes and obesity [31,32]. Thus, our data agree with previous findings [33]. In the 301 Type II diabetic patients, the mutant group of -786T-C polymorphism showed a higher HbA 1c than the non-mutant group.…”
Section: Discussionsupporting
confidence: 92%
“…There is increasing evidence that NO synthesis and the vasodilating properties of insulin are impaired in insulin resistant states, such as Type II diabetes and obesity [31,32]. Thus, our data agree with previous findings [33]. In the 301 Type II diabetic patients, the mutant group of -786T-C polymorphism showed a higher HbA 1c than the non-mutant group.…”
Section: Discussionsupporting
confidence: 92%
“…24 Second, the ischemic damage can be further amplified by insulin resistance that has been related to a lower ability of insulin to induce vasodilatation through impaired nitric oxide endothelial production or accelerated inactivation. 25 The relationship between DR and cardiovascular autonomic function has been examined in earlier studies using HRV analysis. 26,27 Schmidt et al 26 have shown that DR is associated with heart rate response by electrocardiographical monitoring in type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The differ- ence in NO production between our results and the previous report may be due to rat strain or the period of experiment. Insulin resistance was expected to be enhanced by the change of leptin, TNF-a and NO [12,18,32,33]. To evaluate insulin resistance, we used the HOMA-R, which is well correlated with M-values obtained by euglycemic hyperinsulinemic clamp [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in NO production observed in rats following exercise training has been known to improve insulin resistance and leptin resistance in diabetes mellitus and obesity [32]. Urinary NO excretion decreases in parallel with the progression of insulin resistance in human type 2 diabetes [33]. Therefore, NO is suggested to be related to the pathogenesis of diabetes.…”
mentioning
confidence: 99%